178k views
5 votes
-5/4x - 2)=-2(3 +6x)

User Davlog
by
6.0k points

1 Answer

5 votes

Answer:

x = (-16)/43

Explanation:

Solve for x:

(-5 x)/4 - 2 = -2 (6 x + 3)

Put each term in (-5 x)/4 - 2 over the common denominator 4: (-5 x)/4 - 2 = (-5 x)/4 - 8/4:

(-5 x)/4 - 8/4 = -2 (6 x + 3)

(-5 x)/4 - 8/4 = (-5 x - 8)/4:

(-5 x - 8)/4 = -2 (6 x + 3)

Multiply both sides by 4:

(4 (-5 x - 8))/4 = -2×4 (6 x + 3)

(4 (-5 x - 8))/4 = 4/4×(-5 x - 8) = -5 x - 8:

-5 x - 8 = -2×4 (6 x + 3)

4 (-2) = -8:

-5 x - 8 = -8 (6 x + 3)

Expand out terms of the right hand side:

-5 x - 8 = -48 x - 24

Add 48 x to both sides:

48 x - 5 x - 8 = (48 x - 48 x) - 24

48 x - 48 x = 0:

48 x - 5 x - 8 = -24

48 x - 5 x = 43 x:

43 x - 8 = -24

Add 8 to both sides:

43 x + (8 - 8) = 8 - 24

8 - 8 = 0:

43 x = 8 - 24

8 - 24 = -16:

43 x = -16

Divide both sides of 43 x = -16 by 43:

(43 x)/43 = (-16)/43

43/43 = 1:

Answer: x = (-16)/43

User Pierre Guilbert
by
5.2k points